Nash type games in competitive facilities location. (2016) - Karakitsiou, Athanasia; Migdalas, Athanasios
In a non-cooperative game, a Nash equilibrium corresponds to a set of strategies, which ensure that none of the players are better off by unilaterally changing his strategy. This work focuses on the application of Nash Equilibrium to the competitive facility location. Its aim is to provide an up to date review of the literature concerning the discrete version of the problem.